Two polymorphs of 5‐cyclohexyl‐5‐ethylbarbituric acid and their packing relationships with other barbiturates. Issue 3 (17th February 2015) - Gelbrich, Thomas; Meischberger, Isabella; Griesser, Ulrich J.
<x xml:space="preserve">Abstract</x> Polymorph (Ia) (m.p. 474 K) of the title compound, C12H18N2O3, displays an N—H...O=C hydrogen‐bonded layer structure which contains R66(28) rings connecting six molecules, as well as R22(8) rings linking two molecules. The 3‐connected hydrogen‐bonded net resulting from these interactions has the hcb topology. Form (Ib) (m.p. 471 K) displays N—H...O=C hydrogen‐bonded looped chains in which neighbouring molecules are linked to one another by two different R22(8) rings. Polymorph (Ia) is isostructural with the previously reported form II of 5‐(2‐bromoallyl)‐5‐isopropylbarbituric acid (noctal) and polymorph (Ib) is isostructural with the known crystal structures of four other barbiturates.